Помогите сделать: 1)Найдите значение выражения: ху- х²-2у+2х, при х==2⅔; у=3⅔ 2)Решите уравнение: х²(х+2)-(х+2)(х²-2х+4)-2х²+4х=0

Помогите сделать: 1)Найдите значение выражения: ху- х²-2у+2х, при х==2⅔; у=3⅔ 2)Решите уравнение: х²(х+2)-(х+2)(х²-2х+4)-2х²+4х=0
Гость
Ответ(ы) на вопрос:
Гость
1) упростим выражение : xy -x²-2y+2x= x(y-x) -2(y-x) = (x-2)(y-x) при х = 2  2/3  ; у=3  2/3 (2  2/3  -  2)( 3   2/3   -  2   2/3 ) = 2/3  *  1 = 2/3 2)  х²(х+2) - (х+2)(х²-2х+4) -2х²+4х=0 х³+2х² - (х³+8)  -2х²+4х=0 х³+4х -х³-8=0 4х-8=0 4х=8 х=8/4 х=2
Гость
N 1 1) xy - x^2 - 2y + 2x = x( y - X ) - 2( y - X ) = ( y - X )( X - 2 ) 2) X = 2 2/3 = 8/3 ; y = 3 2/3 = 11/3 ( 11/3 - 8/3 )( 2 2/3 - 2 ) = 1•2/3 = 2/3 Ответ 2/3 N 2 X^2( X + 2 ) - ( X + 2 )•( x^2 - 2x + 4 ) - 2x^2 + 4x = 0 ( X + 2)•( x^2 - ( x^2 - 2x + 4 ) - 2x^2 + 4x = 0 ( X + 2 )( 2x - 4 ) - 2x•( X - 2 ) = 0 ( X + 2 )•2•( X - 2 ) - 2x•( X - 2 ) = 0 ( X - 2 )•( 2( x + 2 ) - 2x ) = 0 ( X - 2)•( 2x + 4 - 2x ) = 0 4•( X - 2 ) = 0 X = 2 Ответ 2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы